2005
DOI: 10.1002/cncr.21116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunohistologic typing of salivary duct carcinoma

Abstract: BACKGROUNDDue to the low incidence of salivary duct carcinoma (SDC), only limited data in regard to the biologic behavior of this tumor and its immunohistochemical characteristics are available. The authors analyzed the clinical, molecular, and genetic profile of SDC and identified prognostic factors.METHODSThe follow‐up of 50 patients with SDC was obtained and paraffin‐embedded tumor samples were examined immunohistochemically. In all samples, the expression of Ki‐67, HER‐2, and the oncoproteins p16 and p53 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
350
7
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(390 citation statements)
references
References 33 publications
30
350
7
3
Order By: Relevance
“…Notably, the present analysis determined a good short-term outcome for the patients with primary SDC, which was in disagreement with the findings reported in previous studies (2,3,6,7,(10)(11)(12)(13). Mortality in late-stage patients was 22.2% compared with 0% in early-stage patients with similar prognoses; however, N status did not appear to have a significant impact on the patient prognosis.…”
Section: A B C D Econtrasting
confidence: 99%
See 2 more Smart Citations
“…Notably, the present analysis determined a good short-term outcome for the patients with primary SDC, which was in disagreement with the findings reported in previous studies (2,3,6,7,(10)(11)(12)(13). Mortality in late-stage patients was 22.2% compared with 0% in early-stage patients with similar prognoses; however, N status did not appear to have a significant impact on the patient prognosis.…”
Section: A B C D Econtrasting
confidence: 99%
“…A number of previous studies demonstrated that HER-2/neu and p53 expression are statistically associated with SDC survival rates (3,(15)(16)(17)(18)(19)(20). However, in the present study, the protein expression levels of HER-2/neu, AR, Ki-67, p16 and p53 did not correlate with prognosis, although HER-2/neu, AR and p16 demonstrated a positive expression rate of >50%, which may contribute to the diagnosis for SDC.…”
Section: A B C D Econtrasting
confidence: 82%
See 1 more Smart Citation
“…Various studies of HER-2 in SDC have shown variable results, with amplification occurring in 25-100% of tumors (Jaspers et al, 2011). Nonetheless, the proportion is much higher than that observed in the other histological subtypes, such as the ACCs and MECs described above (Etges et al, 2003;Giannoni et al, 1995;Gibbons et al, 2001;Glisson et al, 2004;Hellquist et al, 1994;Jaehne et al, 2005;Locati et al, 2009;Milanoet al, 2007;Nguyen et al, 2003;Press et al, 1994;Skalova et al, 2001;Williams et al, 2007). HER-2 expression is considered to correlate with histological grade in both salivary gland neoplasms as well as breast cancer, and represents a potential attractive therapeutic approach for SDCs.…”
Section: Salivary Duct Carcinoma (Sdc)mentioning
confidence: 98%
“…3 Estudios inmuno-histoquímicos para detectar la expresión de proteínas reguladoras del ciclo celular demuestran que la pRB2/p130 tiene una influencia estadísticamente significativa en la presencia de metás-tasis y en la patogénesis y progresión de algunas neoplasias de glán-dulas salivares. 4 El factor de crecimiento endotelial vascular muestra una asociación con la expresión del p53 y tiene valor pronósti-co en los carcinomas de glándulas salivares.…”
unclassified